Question
upstudy study bank question image url

Find the derivative of the function \( G(x)=\left(9+\left(1+4 x^{8}\right)^{5}\right)^{6} \)

Ask by Bird Lawson. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( G(x) \) is \( G'(x) = 960x^7(1 + 4x^8)^4[9 + (1 + 4x^8)^5]^5 \).

Solution

We start with the function:   G(x) = [9 + (1 + 4x⁸)⁵]⁶ This function is a composition of multiple functions. We will use the chain rule step-by-step. Step 1: Let   u(x) = 9 + (1 + 4x⁸)⁵ Then, G(x) = [u(x)]⁶. Differentiating G with respect to x gives:   G'(x) = 6[u(x)]⁵ · u'(x). Step 2: Differentiate u(x):   u(x) = 9 + (1 + 4x⁸)⁵ Notice that the derivative of 9 is 0, and for (1 + 4x⁸)⁵ we apply the chain rule again. Let:   v(x) = 1 + 4x⁸ So, (1 + 4x⁸)⁵ becomes [v(x)]⁵. Differentiate:   d/dx[v(x)]⁵ = 5[v(x)]⁴ · v'(x). Step 3: Differentiate v(x):   v(x) = 1 + 4x⁸ Thus,   v'(x) = 32x⁷    (since the derivative of 4x⁸ is 32x⁷). Step 4: Combine these results:   u'(x) = d/dx[(1 + 4x⁸)⁵] = 5(1 + 4x⁸)⁴ · 32x⁷        = 160x⁷(1 + 4x⁸)⁴. Step 5: Substitute u(x) and u'(x) back into the derivative for G(x):   G'(x) = 6[u(x)]⁵ · u'(x)       = 6[9 + (1 + 4x⁸)⁵]⁵ · 160x⁷(1 + 4x⁸)⁴. Multiply the constants:   6 × 160 = 960. So, the final derivative is:   G'(x) = 960x⁷(1 + 4x⁸)⁴[9 + (1 + 4x⁸)⁵]⁵. This is the derivative of the function G(x).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of the function \( G(x) = \left(9 + \left(1 + 4x^{8}\right)^{5}\right)^{6} \), we can use the chain rule. First, we differentiate the outer function: 1. Let \( u = 9 + \left(1 + 4x^{8}\right)^{5} \), then \( G(x) = u^{6} \). 2. The derivative \( G'(x) = 6u^{5} \cdot \frac{du}{dx} \). Next, we need to find \( \frac{du}{dx} \): 1. \( \frac{du}{dx} = \frac{d}{dx}\left(9 + \left(1 + 4x^{8}\right)^{5}\right) = 0 + 5\left(1 + 4x^{8}\right)^{4} \cdot \frac{d}{dx}(1 + 4x^{8}) \). 2. Next, differentiate \( 1 + 4x^{8} \): \( \frac{d}{dx}(1 + 4x^{8}) = 32x^{7} \). 3. Thus, \( \frac{du}{dx} = 5\left(1 + 4x^{8}\right)^{4} \cdot 32x^{7} = 160x^{7}\left(1 + 4x^{8}\right)^{4} \). Now substitute back into the derivative of \( G(x) \): \[ G'(x) = 6\left(9 + \left(1 + 4x^{8}\right)^{5}\right)^{5} \cdot 160x^{7}\left(1 + 4x^{8}\right)^{4}. \] Finally, we can combine and simplify: \[ G'(x) = 960x^{7}\left(9 + \left(1 + 4x^{8}\right)^{5}\right)^{5}\left(1 + 4x^{8}\right)^{4}. \] So the derivative is: \[ G'(x) = 960x^{7}\left(9 + \left(1 + 4x^{8}\right)^{5}\right)^{5}\left(1 + 4x^{8}\right)^{4}. \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy